Peranan Mineral Seng Terhadap Outcome Kehamilan Pada Ibu Hamil Anemia - Dewi, Ratna Candra (Pergizi Pangan DPD NTT, 2009)
This research was aimed to find out the role of Tablet Tambah Darah (TTD) and zinc supplementation for two months on pregnancy outcome (weight birth, length birth and Apgar Score). This research was an experimental study with a pretest-posttest control group design and double-blind method. The samples were taken from anemia pregnant woman subpopulation with begin the gestation from 30-31 weeks, not suffered diseases, and Hb level of < 11 g%. The samples consist of 20 subjects, taken by the use of simple random sampling and the samples were divided into two groups. 10 samples were control group that received TTD supplementation and 10 samples were treatment group that received TTD and zinc supplementation. Nutrient consumption data was collected by 24 hours recall method and food frequency questionnaire. Data was analyzed using Paired Sample t test and independent sample t test. The research result showed highly significant difference of body weight and nutrient consumption (energy, protein, and iron) in pretest and post test each group with p value in all group showed p<0,05. The result also showed significant difference of post protein consumption (p=0,009), weight birth (p=0,005), and length birth (p=0,003) between two groups.